Construction and evaluation of a bioluminescent Pseudomonas aeruginosa reporter for use in preservative efficacy testing. Issue 8 (12th August 2021) - Rushton, Laura; Donoghue, Denise; Bull, Matthew; Jay, Peter; Mahenthiralingam, Eshwar
Abstract : Preservative efficacy testing (PET) is a fundamental practice in industrial microbiology used to ensure product shelf-life and quality. To improve on current growth-based PET, bioluminescence was evaluated as a real-time bacterial viability indicator using Pseudomonas aeruginosa . Random mutagenesis of an industrial P. aeruginosa strain with a promoter-less luxCDABE mini-Tn5 was used to select a stable reporter (LUX12H5) with an un-altered growth and preservative susceptibility phenotype. Bioluminescence and viability were measured with and without preservatives (isothiazolinones, phenoxyethanol, and dimethyl dimethylol hydantoin) and an antibiotic comparator (ciprofloxacin). In the absence of antimicrobials, a good correlation between bioluminescence and viability (r 2 =0.92) was established. However, metabolic inhibition by isothiazolinone preservatives caused a rapid decline in light output that did not correlate to a reduced viability. Conversely, after ciprofloxacin exposure, the decline in viability was greater than that of bioluminescence. A positive attribute of the bioluminescence was the early detection of metabolic recovery and re-growth of preservative injured bacteria. Overall, while initial bioluminescence read-outs were less suited to current PET requirements, it shows promise as an early, direct indicator of bacterial regrowth in the context of long-term evaluation of preservative efficacy.